Exploring Spoken English Learner Language Using Corpora : Learner Talk - Friginal, Eric; Lee, Joseph J.; Polat, Brittany; Roberson, Audrey (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a corpus-based study of spoken learner language produced by university-level ESL students in the classroom. Using contemporary theories as a guide and employing cutting-edge corpus analysis tools and methods, the authors analyse a variety of learner speech to offer many new insights into the nature and characteristics of the spoken language of college ESL learners. Focusing on types of speech that are rarely examined, this original work makes a significant contribution to the study and understanding of ESL spoken language at university level. It will appeal to students and scholars of applied linguistics, corpus linguistics, second language acquisition and discourse analysis.
Keywords: Linguistics.; Applied linguistics.; Discourse analysis.; Multilingualism.; Corpora (Linguistics).; Teaching.; elektronické knihy; electronic books